Intracardiac migration of a ventriculoperitoneal shunt - Joseph Sahagun (Elsevier, 2022)
Here our group presents a rarely encountered case of ventriculoperitoneal shunt migration into the right atrium and ventricle of the heart. Being a large volume neurosurgical center, shunting procedures are commonplace in the operating theater, the vast majority of which are uncomplicated and thus could be considered “routine”. Yet, to date, we have not encountered this phenomenon and thus present this for awareness of the possibility of trans-subclavian cannulation with normal VPS distal terminus confirmation with subsequent migration into the heart. We also propose methods for perioperative workup and intraoperative management of such complications. This is of importance in the neurosurgical management as supra-diaphragmatic terminus of the VPS can occur in diaphragmatic hernia or shunt migration as we describe, the latter requiring removal.